2023
DOI: 10.3892/etm.2023.11978
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics, molecular features and novel diagnostic strategies for the detection of malignant transformation of endometriosis (Review)

Abstract: Endometriosis is a benign gynecological disease that affects women of reproductive age. Although malignant transformation of endometriosis is rare, physicians must be aware of this due to the high incidence of clear cell carcinoma of the ovary (CCC) in Japan. The most prevalent histological subtype of ovarian cancer is CCC (~70%) followed by endometrioid carcinoma (30%). The present review discusses the clinicopathological and molecular features of endometriosis-associated ovarian cancer (EAOC) as well as pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 85 publications
(205 reference statements)
0
3
0
8
Order By: Relevance
“…Recent research has identified several key molecular drivers in the malignant transformation from endometriosis to clear cell carcinoma, including ARID1A mutations, PIK3CA mutations, inactivating PTEN mutations and HNF-1β activation ( 24 , 29 ). The ongoing advancements in genomics and molecular biology are poised to uncover additional mechanisms underlying the malignant transformation of endometriosis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified several key molecular drivers in the malignant transformation from endometriosis to clear cell carcinoma, including ARID1A mutations, PIK3CA mutations, inactivating PTEN mutations and HNF-1β activation ( 24 , 29 ). The ongoing advancements in genomics and molecular biology are poised to uncover additional mechanisms underlying the malignant transformation of endometriosis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Приблизно у 1% випадків ендометріоз асоціюється зі злоякісним ураженням яєчників [6]. І хоча таке явище, як трансформація ендометріозу у злоякісний процес відбувається нечасто, це потрібно брати до уваги [7].…”
Section: а к т у а л ь н і т е м иunclassified
“…На сьогодні встановлено тісний причинно-наслідковий зв'язок між ендометріоїдним ураженням яєчників та появою епітеліального типу раку яєчників, а саме -ендометріоїдної карциноми та світлоклітинної карциноми [8][9][10][11][12][13][14]. Ендометріоїдну та світлоклітинну карциноми прийнято об'єднувати у термін «ендометріоз-асоційований рак яєчників», бо ендометріоз є їхнім попередником [7,15]. М. Hermens et al зазначають, що при ендометріозі яєчників існує ризик появи не тільки ендометріоїдних та світлоклітинних карцином, а взагалі всіх підтипів злоякісного ураження яєчників [10].…”
Section: а к т у а л ь н і т е м иunclassified
See 1 more Smart Citation
“…16 In contrast, TFPI2 is overexpressed in epithelial ovarian cancer, especially in ovarian clear cell carcinoma (CCC), and elevated serum TFPI2 levels are thought to reflect TFPI2 overexpression in CCC tissue. [17][18][19][20][21][22] Therefore, TFPI2 has emerged as a clinically available serodiagnostic marker capable of distinguishing between benign and malignant ovarian tumors, especially CCC. 15,22 After clinical trials, TFPI2 testing has been covered by the Japanese National Health Insurance since April 2021.…”
Section: Introductionmentioning
confidence: 99%